Acute neuromuscular responses to car racing - Backman, Jani (2005)
Purpose: The primary purpose of this study was to determine racing car drivers’ acute neuromuscular responses to race driving. The secondary purpose was to compare the cardiovascular loading of driving to that of maximal rowing action. Methods: The subjects of the present cross-sectional study (n = 9) were international level karting drivers. The study was performed in two parts; the laboratory tests and driving test. All subjects took part to the laboratory tests and five of the subjects performed also the driving test. The rowing tests consisted of indoor rowing started at the power of 90 watts and the load was increased 30 watts every third minute until voluntary exhaustion. In the driving test each driver drove with his own kart for 30 minutes in a simulated full speed race including one pit stop in a halfway. The strength test protocol consisted of five maximal voluntary contraction (MVC) isometric strength tests (neck lateral flexion to right, shoulder flexion, grip strength, bilateral leg extension and bilateral plantar flexion). The same strength test protocol was accordingly made four times; before and after the maximal rowing test and before and after the driving. Results: Average maximal oxygen consumption (VO2max) of the rowing test was 47,6 ± 5,4ml/kg/min and maximal rowing heart rate was 189 ± 5bpm. In the driving test, average heart rate of 30 minutes of driving was 139 ± 12bpm. Maximal blood lactate (bLa) in rowing was 12,2 ± 2,1mmol/l and 3,3 ± 1,7mmol/l after 15 minutes of driving and 3,1 ± 1,6 at the end of driving. Maximal strength was found to decrease systematically both after rowing and driving. The decrease in maximal strength was systematically more after driving than rowing. Significant differences between the driving and rowing-induced changes were found in shoulder and plantar flexor strength actions. The decrease in the change of the force-time curve was significant (p<0.05 and p<0.01) between pre and post driving in shoulder test. Conclusion: The present results indicate that considerable loading of the neuromuscular system takes place in competitive driving. This study also indicates that while there is high physiological and moderate neuromuscular loading in maximal rowing, competitive race driving seems to be characterised by moderate physiological and high neuromuscular loading. Driving seems to strain the neuromuscular system due to G-forces and vibration.